Literature Review: Hubungan Usia, Keparahan Benign Prostate Hyperplasia (BPH) dan Kejadian Disfungsi Ereksi - Winda Wati; Eka Yudha Rahman; Lena Rosida; Hendra Sutapa; Roselina Panghiyangani (Homeostasis, 2021)
Abstract: Benign prostate hyperplasia (BPH) is considered a degenerative disease. A problem that often occurs in men as they get older, BPH can cause erectile dysfunction in patients. This literature review generally aims to see the relationship between age and severity of BPH and the incidence of erectile dysfunction. The search was carried out on articles in English and Indonesian published between 2011-2020 in the Pubmed, Science Direct and Google Scholar databases. The articles used in this literature review are 22 articles. The results of literature review show that there is a relationship between age and BPH, with increasing age the incidence of BPH is also higher, besides that there is also a relationship between the severity of BPH and the incidence of erectile dysfunction. The incidence of erectile dysfunction increases significantly with the severity of BPH and the higher the IPSS score, the lower the IIEF 5 score will be. Keywords: Benign Prostate Hyperplasia (BPH), Lower Urinary Tract Symptoms (LUTS), erectile dysfunction. Abstrak: Benign Prostate Hyperplasia (BPH) dianggap sebagai penyakit degeneratif. Permasalahan yang sering terjadi pada pria seiring dengan pertambahan usia, BPH dapat menyebabkan terjadinya disfungsi ereksi pada pasien. Tinjauan literatur ini secara umum bertujuan untuk mengetahui hubungan usia dan keparahan BPH dengan kejadian disfungsi ereksi. Penelusuran dilakukan pada artikel berbahasa Inggris dan Indonesia yang diterbitkan antara tahun 2011-2020 pada database Pubmed, Science Direct dan Google Scholar. Artikel yang digunakan dalam tinjauan literatur ini sebanyak 22 artikel. Hasil tinjauan literatur menunjukkan bahwa terdapat hubungan antara usia dengan terjadinya BPH, semakin bertambahnya usia maka insidensi menderita BPH juga semakin tinggi, selain itu terdapat pula hubungan antara keparahan BPH dengan kejadian disfungsi ereksi. Insidensi disfungsi ereksi meningkat secara signifikan sejalan dengan keparahan BPH dan semakin tinggi skor IPSS maka skor IIEF 5 akan semakin menurun. Kata-kata kunci: Benign Prostate Hyperplasia (BPH), Lower Urinary Tract Symptoms (LUTS), disfungsi ereksi.